Enhanced electrochemical performance in microbial fuel cell with carbon nanotube/NiCoAl-layered double hydroxide nanosheets as air-cathode. (22nd October 2021) - Chen, Junfeng; Jiang, Liting; Yang, Jiaqi; Wang, Xuemei; An, Ying; Yang, Daoxin; Wei, Qingying; Wang, Yongle; Wang, Renjun; Yang, Yuewei; Liu, Yanyan
Abstract: The ternary component NiCoAl-layered double hydroxide (NiCoAl-LDH) and carbon nanotube (CNT) nano-composite (CNT/NiCoAl-LDH) were successfully prepared by a simple hydrothermal method. The NiCoAl-LDH nanosheets were effectively and uniformly grown on CNTs, forming a cross-linked conductive network structure, and stainless steel (SS) mesh was used as the base to load CNT/NiCoAl-LDH for microbial fuel cell (MFC) cathode. X-ray diffraction (XRD) results presented that the CNT/NiCoAl-LDH hybrid exhibited the (003), (006), (012), (015), (018), (110) and (113) crystal planes of hydrotalcite reflection. The surface functional groups C-O, C=O, C-H, C-N and M-O of the hybrid were confirmed. The cross-linked network structure of the hybrid was observed and the content and proportion of each element of the hybrid were found. CNT/NiCoAl-LDH showed excellent catalytic oxygen reduction reaction (ORR) ability by cyclic voltammetry (CV) and linear voltammetry (LSV) due to its abundant electrochemical active sites and excellent conductivity. The maximum output voltage of CNT/NiCoAl-LDH catalyst as MFC cathode was 450 mV, the maximum power density was 433.5 ± 14.8 mW/m 2, and the maximum voltage stabilization time was 7–8 d. The results indicated that the CNT/NiCoAl-LDH hybrid was full potential as a high-performance, low-cost MFC cathode catalyst in future. Graphical abstract: Image 1 Highlights: In-situ growth of NiCoAl-LDH nanosheets on CNT surface by hydrothermal method. CNT/NiCoAl-LDH catalyst has amazing stability and durability in the MFC cathode. Maximum power density produced by CNT/NiCoAl-LDH-MFC was 433.5 ± 14.8 mW/m 2 . Fully exposed active sites and high conductivity improve MFC performance.